182. Study of the accuracy of non-invasive fixation frames in brain treatments with Helical Tomotherapy. (December 2018) - Iacco, M.; Zucchetti, C.; Lupattelli, M.; Aristei, C.; Tarducci, R.
Abstract: Purpose: The study focused on the accuracy of intracranial frame-less radiosurgery (RS) and intracranial hypo-fractionated treatments (HFT), delivered with helical Tomotherapy (HT), by means of two different mask-based fixation systems (FPM = Five Point Mask and DSPS = Double Shell Positioning System). Methods: A Megavoltage Computed Tomography (MVCT) was acquired and automatically registered with the planning CT of a Rando phantom, to evaluate the delivery accuracy of the HT image guided positioning tool. After the application of the suggested shifts, the phantom was scanned a second time and shifts in each direction and rotations were recorded; the vector displacement ( v ) was calculated as the square sum of the shifts in each directions. Analogous procedure was applied to 14 and 16 patients underwent intracranial HFT and RS respectively: overall 59 MVCT performed at the end of the treatment were acquired and analyzed. The v were analyzed in order to evaluate the intra-fraction motions. Results: The mean v, obtained in the phantom acquisitions, was 0.4 ± 0.2 mm, showing that HT-IGRT system is able to achieve positioning accuracy typical of RS ( v < 1 mm ). Moreover, the mean rotational variations were negligible. Results on the patient treatments, reported in Table 1, showed that both masks minimized the intra-fraction motion to an extent of 1 mm (with no statistically difference between FPM and DSPS: p < 0.573, Mann-Whitney Test). No dependence of v on the treatment time was observed. Conclusions: Our study demonstrates that mask-based fixation systems have a high intracranial positioning accuracy, comparable with for invasive immobilization systems (v = 0.6 ± 0.9 mm (range: 0.3–1.7 mm)[1] ), therefore, they could be used for high-precision treatments, like RS.